Meta Analisis: Pengaruh Model Discovery Learning Terhadap Peningkatan Kemampuan Berpikir Kritis Matematika: Meta Analysis: The Effect Of Discovery Learning Model On Increasing Mathematics Critical Thinking Ability - Suwarno Zul Hanifah; Kristanti Febriana; Soemantri Sandha (Pendidikan Matematika Universitas PGRI Yogyakarta, 2022)
The condition of Indonesian students' critical thinking skills is ranked 6th lowest with an average score of 379 on PISA 2018. The lack of students' critical thinking skills is found in learning that is still one-way using conventional models. This makes students less enthusiastic about listening and understanding the material presented. These conditions can be trained by applying exploratory learning so that students can find and understand, and solve problems. One learning model that can foster critical thinking skills in students is the discovery learning model which can support students to be maximally involved in identifying and organizing the way students learn to discover knowledge concepts. This study aimed to determine the effect of the discovery learning model on students' critical thinking skills using the Systematic Literature Review method according to the exclusion criteria and found 12 articles obtained through Google Scholar. The results of the meta-analysis show that the discovery learning model influences students' critical thinking skills at every level of education. The discovery learning model has the highest effect on elementary education level flat material with an effect size of 1.9. The junior high school level shows the highest effect size of 2.1 with social arithmetic material. The SMA/SMK level gives the highest effect of 1.18 in statistics. It can be concluded that the discovery learning model influences critical thinking skills in mathematics. Keywords: Critical Thinking, Discovery Learning, Mathematics